2016
DOI: 10.1021/acs.jpcc.6b02077
|View full text |Cite
|
Sign up to set email alerts
|

Conduction and Surface Effects in Cathode Materials: Li8ZrO6 and Doped Li8ZrO6

Abstract: Doped Li8ZrO6 (LZO) is a pseudolayered material under consideration for lithium-ion battery cathodes and solid electrolyte coatings. The effects of doping LZO with Ce, Ti, Mg, Nb, and Y on structure, band gaps, conductivity, and activation energy for ion migration are investigated both experimentally and by quantum mechanical calculations. Optical band gaps decrease for all doped materials compared to undoped LZO. While all dopants reduce the electronic conductivity at room temperature slightly, doping with Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…The movement of the vacancy involves the migration of Li + from an occupied site to a vacant site; thus, vacancy diffusion is described in terms of the simultaneous movement of a Li + and a hole polaron. We considered two such diffusion processes: (a) a cross process, in which the paths of the Li + and the polaron cross and (b) a side-by-side (SBS) process, in which the paths of Li + and the polaron are parallel . The results are given in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The movement of the vacancy involves the migration of Li + from an occupied site to a vacant site; thus, vacancy diffusion is described in terms of the simultaneous movement of a Li + and a hole polaron. We considered two such diffusion processes: (a) a cross process, in which the paths of the Li + and the polaron cross and (b) a side-by-side (SBS) process, in which the paths of Li + and the polaron are parallel . The results are given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…For calculations on surfaces of LSO, based on our previous tests, 19 a vacuum layer of 10 Å was used to remove any interaction between the periodically repeated slabs of the most stable (0001) surface, and the five bottom layers of the slab were fixed at the positions in the bulk structure. A 3 × 3 × 1 kpoint mesh was used for the k-point sampling.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…These U values are adopted according to the simulation parameters of Li­(Ni x Mn y Co z )­O 2 models from the Materials Project Web site () and our own tests . Recent studies reported that for some kinds of TM oxides as cathode materials (e.g., Li 8 ZrO 6 ), applying U to p orbitals of oxygen during charging can give a correct picture of oxygen polaron but that PBE cannot. We tested and applied U (1 eV) to p orbitals of oxygen for (333) at SOC = 0.33 and 0.66, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%